Tanggung Jawab Badan Hukum Perseroan Terbatas Dalam Keadaan Pailit - Almas Qinthar Tri Cipto; Sumriyah Sumriyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2023)
Bankruptcy occurs when a debtor is unable to pay his debts to creditors. Countries can also experience financial difficulties leading to bankruptcy. The purpose of the bankruptcy process in a limited company is to speed up the liquidation process and distribution of company assets to creditors. As a corporation that has characteristics like private law, a limited company separates its assets from the management of the company. However, if the limited company goes bankrupt and disbands, can the management of the company still be held accountable or not?